2011
DOI: 10.1007/s11258-011-9896-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, diversity, and resource gradient relationships in the herbaceous layer of an old-growth Appalachian forest

Abstract: The ecological drivers of herbaceous layer composition and diversity in deciduous forests of eastern North America are imperfectly understood. We analyzed the herbaceous layer, across the growing season, in a central Appalachian old-growth forest to examine dynamics, diversity, and relationships to resource gradients. We found clear variation in herb species composition over the growing season. We identified intermingled resource gradients, including soil nutrients, light availability, and topography, that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
(103 reference statements)
2
28
0
Order By: Relevance
“…Gilliam et al (1995) suggested a mechanism for linkage among forest vegetation that emphasized the importance of gradients of environmental factors. In essence, linkage is predicted to arise when forest strata respond to similar gradients in a similar fashion, a contention that has been supported in the literature (Barbier et al 2008, Burton et al 2011, McEwan and Muller 2011, Vockenhuber et al 2011, Jackson et al 2012, Bartels and Chen 2013. The lack of linkage between overstory and herb layer for both slope aspects is also consistent with this prediction, considering that these strata appear to respond to different environmental gradients: the herb layer on the NE aspect was more influenced by extractable NO 3 À and soil OM, whereas the overstory was influenced more by soil pH and moisture.…”
Section: Patterns Of Linkage Among Biotic Communitiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Gilliam et al (1995) suggested a mechanism for linkage among forest vegetation that emphasized the importance of gradients of environmental factors. In essence, linkage is predicted to arise when forest strata respond to similar gradients in a similar fashion, a contention that has been supported in the literature (Barbier et al 2008, Burton et al 2011, McEwan and Muller 2011, Vockenhuber et al 2011, Jackson et al 2012, Bartels and Chen 2013. The lack of linkage between overstory and herb layer for both slope aspects is also consistent with this prediction, considering that these strata appear to respond to different environmental gradients: the herb layer on the NE aspect was more influenced by extractable NO 3 À and soil OM, whereas the overstory was influenced more by soil pH and moisture.…”
Section: Patterns Of Linkage Among Biotic Communitiesmentioning
confidence: 86%
“…When this occurs, the strata are said to exhibit linkage. This has commonly been reported for overstory and herbaceous strata for a variety of forest ecosystems (Gilliam 2007, McEwan and Muller 2011, Vockenhuber et al 2011, Jackson et al 2012, Gilliam and Roberts 2014, with far fewer studies including soil microbial communities in their analyses. Linkage is commonly assessed via multivariate statistics (e.g., ordination), wherein axes scores from separate overstory and herb layer analyses are subjected to correlation and linkage being assumed from significant correlation between axis scores (Barbier et al 2008).…”
Section: Introductionmentioning
confidence: 92%
“…tulipifera individuals are found along cove locations and slope bottoms that are more mesic. Many studies have documented differences in soil moisture when comparing microsite habitat variability within forests in the EDF (Kabrick et al , , Groffman et al , , McEwan and Muller ). Our results from Pioneer Mothers suggest that microsite habitat differences might explain the varied climate responses of each species.…”
Section: Discussionmentioning
confidence: 99%
“…The topographic variation underlying these complex gradients is associated with the distribution of coarse woody debris (Muller 2003, Rubino andMcCarthy 2003), fauna (Harper CA and Guynn 1999, Lacki and Schwierjohann 2001, Wood et al 2006, herbaceous vegetation (Small andMcCarthy 2005, McEwan andMuller 2011), soil properties (Hutchins et al 1976), and tree species and forest communities (see the "Biological diversity" section below). have demonstrated substantial changes in topographic complexity as a result of mountaintop mining that have not been quantified across all mountaintop mines in the region.…”
Section: Articlesmentioning
confidence: 99%